Nontraditional Career in Understanding Workers with New Technology - Meta Andriani (Jurnal Ilmu Manajemen & Ekonomika, 2019)
Technology has changed the way people manage both their work and other areas of life.The study analyz-ing the pressure of new technology on the careers of young students from the perspective of career theory. To achieve the objectives of this study, the authors consider the perspective that suggest dividing career theory between traditional and non-traditional. The study involved 111 respondents. The result showed that the variable Self Identity, Perception Competence and Interpersonal Relations together influence the Pres-sure of new technology in a career.